Identification and strategy for the risk mitigation of supply chain with Fuzzy House of Risk: A case study in pallet products - Ulfah, Maria; Bahauddin, Achmad; Trenggonowati, Dyah Lintang; Ekawati, Ratna; Arina, Faula; Sonda, Atia; Ridwan, Asep; Ferdinant, Putro Ferro (Journal Industrial Servicess, 2023)
X Corp. is a manufacturing company that produces various wood packaging products, including pallets, which are in high demand, particularly for export commodities. However, the company's supply chain activities are often affected by various risks. If these risks are not addressed in a timely manner, they could disrupt the supply chain and lead to negative consequences for the company. Therefore, the company management needs to implement supply chain risk management to identify and mitigate these risks. This study aims to identify the risks that have occurred or are likely to occur in the supply chain of X Corp. and determine which risks should be prioritized for mitigation. The fuzzy house of risk method was used to analyze the data. The results of the study identified 38 risk events and 22 risk agents. Additionally, 17 proactive actions were proposed to the company to address the priority risk agents and mitigate their potential impact.